Derived cannabinoid product availability among online vape shops - Nora Satybaldiyeva; Raquel Harati; Tomas Mejorado; Nicolas Morales; Gustavo Benitez; Shannon E. Ellis; Karen Ferran; Eric C. Leas (Preventive Medicine Reports)
Objectives: To determine the proportion of online vape shops that offer derived cannabinoid products in a large metropolitan area (San Diego, California), measure their compliance with state hemp regulations, and estimate whether these shops receive more website traffic compared to those that offered nicotine or tobacco. Methods: We obtained vape shops (n = 109) using browser-based (i.e., Google Search) and map-based (i.e., Google Maps and Yelp) searches in San Diego from March to August 2023 and conducted a content analysis of their websites to identify derived cannabinoid products offered for mail-order purchasing. Using website traffic data, we examined the association between derived cannabinoid product availability and monthly website visits. Results: Among the 109 online vape shops in the study sample, 35.8 % offered derived cannabinoid products for mail-order purchase and 26.6 % sold flavored (excluding terpenes) and inhalable cannabinoid products. Compared to vape shops that did not offer derived cannabinoid products (Mean: 23,619; 95 % CI: 23,605–23,634), those offering flavored and inhalable cannabinoid products received 2.5 times more monthly website visits (Mean: 57,950; 95 % CI: 57,913–57,986) and those offering any derived cannabinoid products received 5.5 times more monthly website visits (Mean: 130,694; 95 % CI: 130,607–130,782). Conclusion: The prevalence of flavored and inhalable derived cannabinoid products, despite being prohibited under California’s hemp regulations, highlights the need for additional enforcement measures to ensure retailer compliance. The higher website traffic observed among vape shops offering cannabinoid products may be indicative of greater popularity of retailers selling derived cannabinoid products compared to those selling nicotine or tobacco products alone.